2000
DOI: 10.1046/j.1524-4725.2000.99211.x
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of EMLA versus ELA-Max for Pain Relief in Medium-Depth Chemical Peeling: A Clinical and Histopathologic Evaluation

Abstract: Both EMLA and ELA-Max decrease the discomfort felt during medium-depth combination chemical peeling without influencing either the clinical or the histopathologic result.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(28 citation statements)
references
References 7 publications
1
25
0
2
Order By: Relevance
“…ELA‐Max® is lidocaine cream that utilizes a patented liposomal delivery system to enhance penetration through the stratum corneum. Early studies showed it effectively decreased the pain associated with dermatological procedures, such as hair removal and chemical peeling (13–15). In addition, an adult volunteer study using a laser as the pain stimulus showed EMLA® and ELA‐Max® provided superior anesthesia at 60 min compared with tetracaine and betacaine‐LA (27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ELA‐Max® is lidocaine cream that utilizes a patented liposomal delivery system to enhance penetration through the stratum corneum. Early studies showed it effectively decreased the pain associated with dermatological procedures, such as hair removal and chemical peeling (13–15). In addition, an adult volunteer study using a laser as the pain stimulus showed EMLA® and ELA‐Max® provided superior anesthesia at 60 min compared with tetracaine and betacaine‐LA (27).…”
Section: Discussionmentioning
confidence: 99%
“…ELA‐Max® (4% lidocaine) is a new topical anesthetic cream that has been shown to decrease pain associated with dermatological procedures (13–15). ELA‐Max® is marketed as being as effective in producing topical anesthesia after a 30‐min application as EMLA® is after a 60 min application (16).…”
Section: Introductionmentioning
confidence: 99%
“…Lidocaine 2.5%/prilocaine 2.5% cream is a eutectic mixture of local anesthetics (EMLA™) and a commonly available topical anesthetic formulation. The efficacy of lidocaine 2.5%/prilocaine 2.5% cream has been shown to be comparable with that of 4% lidocaine alone in a number of procedures, such as prior to chemical peeling, minor surgical procedures, or laser hair removal [18-20]. …”
Section: Introductionmentioning
confidence: 99%
“…13 The new generation of lidocaine for topical administration uses a liposomal encapsulation that facilitates penetration of the active ingredient through intact skin 14 and has shown effective local analgesic properties similar to EMLA cream. [15][16][17] This formulation of lidocaine has a faster onset of peak pain control than EMLA cream (20 minutes) and is effective without the need for occlusive wraps, 17 which makes it a more attractive choice for use in cats.…”
mentioning
confidence: 99%